The relationship between psychological violence by coaches and conformity of young athletes to the sport ethic norms - Fournier, C.; Parent, S.; Paradis, H. (European Journal for Sport and Society, 2021)
The purpose of this study was to explore the relationship between psychological violence by coaches and conformity of athletes to the sport ethic. The objectives of this study are to verify whether the athletes` conformity with sport ethic norms is related to psychological violence by the coach and whether this relationship varies in function of sex and type of sport practiced by the athlete. Athletes (n = 1089) from Canada aged 14-17 years in various sports completed an online questionnaire. Athletes responded to validated scales assessing psychological violence by coaches and conformity to the sport ethic norms. To study the relationship between these two factors, correlations were performed and a multiple linear regression model was used. This study demonstrated associations between the norms `self-sacrifice` and `refusal to accept their limits` and psychological violence by the coach. These relationships were moderated by sex and type of sport. Among girls participating in individual sports, the more they conformed to `self-sacrifice`, the more they experienced psychological violence by the coach. Conversely, among boys participating in team sports, the more they also conformed to this norm, the less they experienced this form of violence. Moreover, regardless of sex, the more athletes participating in individual sports conformed to the `refusal to accept their limits` norm, the less they appeared to experience psychological violence by their coach.